Rationalization of time management and its impact on quality achievement - Messaoud, Nedjimi; Eddine, Doudou Naouri Nour (The International tax journal, 2025)
The current study aims to highlight the impact of rationalizing time management on achieving quality in Algerian organizations. The concept of time management refers to the science of investing time effectively, which is a process based on planning, organizing, coordinating, preparing, directing, following up, and communicating. It is both a quantitative and qualitative process at the same time. However, it is primarily future-oriented, anticipating and predicting prospects, identifying paths and directions, and the various routes leading to goals. Therefore, the path to the future focuses on choosing the right alternatives in the present and using the present as a springboard to the future. Good time management in the future means planning for it in the present, and the planning process in time management means almost complete control over everything in order to achieve the set goals, the most important of which is achieving quality, which in turn reflects the extent and magnitude of the effort and work performed by the organization. Therefore, we will try to shed light on the extent to which time management affects the achievement of quality.